Targeting the Motion of Shikimate Kinase: Development of Competitive Inhibitors that Stabilize an Inactive Open Conformation of the Enzyme - Prado, Verónica; Lence, Emilio; Maneiro, María; Vázquez-Ucha, Juan C; Beceiro, Alejandro; Thompson, Paul; Hawkins, Alastair R; González-Bello, Concepción (Journal of medicinal chemistry, 2016)
The large conformational changes observed by Molecular Dynamics simulation studies on the product release in the LID and shikimic acid binding (SB) domains of the shikimate kinase (SK) enzyme have been exploited in the development of reversible competitive inhibitors against SK from Mycobacterium tuberculosis and Helicobacter pylori. This enzyme is a recognized target for antibiotic drug discovery. The reported C5-substituted shikimic acid analogues interact with the dynamic apolar pocket that surrounds the C4 and C5 hydroxyl groups of the natural substrate, cause the opening of the LID and SB domains, and capture the essential arginine far from the ATP binding site as required for catalysis. The 3-nitrobenzyl 3e and 5-benzothiophenyl derivatives 3i proved to be the most potent inhibitors. An ester prodrug of 3i was the most efficient derivative in achieving good in vitro activity against H. pylori, having a MIC value of 4 μg/mL.